ANALISIS LINGKUNGAN RITEL TERHADAP PERILAKU PEMBELIAN YANG TIDAK TERENCANA (Studi Kasus Pada Konsumen Ramayana Robinson Rajabasa Bandar Lampung) - Bambang Purwanto; Tanti Astuti (GEMA : Jurnal Gentiaras Manajemen dan Akuntansi, 2017)
Marketers need a proper strategy that consumers are interested in making a purchase unplanned.Thepurpose of this study was to determine the effect of retail environments against unplanned purchasingbehavior. The study population is consumer Rajabasa Ramayana Robinson in Bandar Lampung andresearch respondents as many as 91 samples. Data collection instrument using a questionnaire withLikert scale that has been qualified validity and reliability as well as an analysis tool used is multiplelinear regressionT test results with a confidence level of 95% or α <0.05. The layout of the positive and significant effectto the results of statistical analysis tcount (2,253), saleswoman positive and significant impact with theresults tcount (2.335), a significant negative effect lighting with tcount (-2.601), music with a positive andsignificant effect tcount (2.133), aroma positively and significantly with tcount (2.255), the temperature doesnot affect the acquisition results tcount (-1.075), display significant negative effect with tcount (-2.772), signsof significant positive effect with tcount (2.052) and display of color has no effect with the acquisition tcount(1,102). F test result Fcount 5.297 and 0.000 significant level (p<0.05), the positive effect of allindependent variables and the dependent variable sigifikan.